2007
DOI: 10.1186/1742-4690-4-50
|View full text |Cite
|
Sign up to set email alerts
|

CD4-independent use of the CCR5 receptor by sequential primary SIVsm isolates

Abstract: Background: CD4-independence has been taken as a sign of a more open envelope structure that is more accessible to neutralizing antibodies and may confer altered cell tropism. In the present study, we analyzed SIVsm isolates for CD4-independent use of CCR5, mode of CCR5-use and macrophage tropism. The isolates have been collected sequentially from 13 experimentally infected cynomolgus macaques and have previously been shown to use CCR5 together with CD4. Furthermore, viruses obtained early after infection were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Lauren et al [37] have suggested the two are interrelated properties for SIVsm, but this is not an absolute requirement. Which of the envelope mutations associated in our experiments with CD4 dependence determine CKR tropism is undefined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lauren et al [37] have suggested the two are interrelated properties for SIVsm, but this is not an absolute requirement. Which of the envelope mutations associated in our experiments with CD4 dependence determine CKR tropism is undefined.…”
Section: Discussionmentioning
confidence: 99%
“…The observed switch from mixed CCR5 and CXCR4 usage in hPBMCs to predominantly CXCR4 usage by both strains has been described for SIV cultured in hPBMCs [ 3 ] , and may be functionally related to acquisition of CD4-dependence [ 25 ] . Lauren et al [ 37 ] have suggested the two are interrelated properties for SIVsm, but this is not an absolute requirement. Which of the envelope mutations associated in our experiments with CD4 dependence determine CKR tropism is undefined.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the ability of CD4-CCR5-VLPs to suppress HIV-1 replication and prevent viral escape in vivo in HIV-1 YU2 –infected humanized mice (hu-mice). CD4-CCR5-VLPs were selected for in vivo experiments to prevent the potential emergence of CD4-independent HIV-1 escape variants ( 28 30 ). To determine an optimal administration regimen, initial half-life studies were performed in uninfected hu-mice.…”
Section: Resultsmentioning
confidence: 99%